### 1 Answer | Add Yours

y = 6x - 3

(-2, -3) Substitute -2 for x and -3 for y.

-3 = 6 * -2 - 3

-3 = -12 - 3

-3 = -15 (false)

The line does not pass through the point (-2, -3).

(0, -3) Substitute 0 for x and -3 for y.

-3 = 6 * 0 - 3

-3 = 0 - 3

-3 = -3 (true)

The line does pass through the point (0, -3).

(1, -3) Substitute 1 for x and -3 for y.

-3 = 6 * 1 - 3

-3 = 6 - 3

-3 = 3 (false)

The line does not pass through the point (1, -3).

**Answer: The line passes through the point (0, -3).**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes